Assessment of consumer knowledge, attitude, perception, and willingness to purchase upcycled foods in Metro Manila - Castulo, Angelica Nicole M.
As food waste continues to increase, upcycled foods are being explored as a sustainable solution. The study aimed to assess Filipino consumers’ knowledge, attitude, perception, and willingness to purchase upcycled foods. A structured questionnaire was developed and administered through QualtricsTM to Filipino consumers (n = 407) from Metro Manila, Philippines. Results indicated that 52.2% of the participants had never heard of upcycled food. Significant differences in knowledge scores, attitude, and nutrition involvement were found between respondents who are aware and unaware of upcycled food. Willingness to purchase was positively correlated with both perception and attitude, while negatively correlated with food neophobia and food technology neophobia. Conversely, perception is positively correlated with attitude, nutrition involvement, and knowledge, while negatively correlated with food neophobia and food technology neophobia. Using Multiple Linear Regression, attitude and knowledge were found to be significant factors of willingness to purchase, while attitude, knowledge, and food technology neophobia were found to be significant factors of perception. These findings can help raise public awareness of upcycled food and provide valuable insights for its development and promotion for public consumption. Further research on other psychological and cultural factors that may influence consumer behavior may be considered. Lastly, communication strategies may be investigated to effectively promote and encourage the development and consumption of upcycled food products.